Perspectives of a Farmer Digital Expert Assistant System - Vigneswaran, Narayanamurthy; Fahmi, Samsuri (ETASR, 2016)
Global positioning system (GPS) based farmer digital expert assistant systems (FDEAS) are capable of analyzing the agricultural field and environmental factors associated with the field. The agricultural yield to be harvested, depends on the liquidity content of the soil, the mineral content of the soil, the geographical position of the field, the microbial content of the soil and the temperature of the environment. Other parameters include irrigation, spraying of chemicals, animals or intruders getting into the field, etc. Such a system monitors all these parameters and provides the appropriate values and suggestions to the farmers. Several factors are monitored using different set of sensors. The location, specified by the GPS, can be compared to existing databases of soil maps and thus provide the nature and type of crop to be cultivated with all specifications to obtain maximum yield at that location. Cameras may be employed to continuously monitor the field and initiate alerts. All sensor outputs and systems can be integrated with a GSM modem which sends alert messages as SMS or recorded audio alerts when required. Such a system would ensure real time monitoring and should provide expert assistance for attaining maximum efficiency. It would act as a holistic system for analyzing, monitoring, alerting and assisting farmers at different stages of farming.